2021
DOI: 10.1029/2021jc017429
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Kuroshio Intrusion on Deep Flow Intraseasonal Variability in the Northern South China Sea

Abstract: Interactions between the open ocean and marginal seas have been suggested to be critical to the redistribution and dissipation of global energy. Here, we propose a mechanism for the upper open ocean influencing the deep flow in marginal seas that hinges on the formation and propagation of topographic Rossby waves (TRWs). Observations and high‐resolution simulations suggest substantial intraseasonal variability with periods of 5–60 days associated with the deep flow over continental slopes of the northern South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Since the variabilities of deep‐water exchange between marginal sea and open ocean have often been linked to upper‐layer processes through vertical coupling (Cai et al., 2023; Hamilton et al., 2019; Quan et al., 2021; Tenreiro et al., 2018), we further computed the deep‐layer LST using satellite‐based ocean bottom pressure difference (∆OBP) between the east (21°N–23°N, 122°E–123°E) and west (19°N–21°N, 120°E–121°E) of the Luzon Strait. The above three modes account for about 92% of the total variance of ∆OBP, and the time series of PC1 (M1) largely correlates (Figure 4e; r = 0.76) with ∆OBP, suggesting that the coherent modes of SSTAs in the NPO and TPO potentially influence the deep‐layer processes in the SCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the variabilities of deep‐water exchange between marginal sea and open ocean have often been linked to upper‐layer processes through vertical coupling (Cai et al., 2023; Hamilton et al., 2019; Quan et al., 2021; Tenreiro et al., 2018), we further computed the deep‐layer LST using satellite‐based ocean bottom pressure difference (∆OBP) between the east (21°N–23°N, 122°E–123°E) and west (19°N–21°N, 120°E–121°E) of the Luzon Strait. The above three modes account for about 92% of the total variance of ∆OBP, and the time series of PC1 (M1) largely correlates (Figure 4e; r = 0.76) with ∆OBP, suggesting that the coherent modes of SSTAs in the NPO and TPO potentially influence the deep‐layer processes in the SCS.…”
Section: Discussionmentioning
confidence: 99%
“…Since the variabilities of deep-water exchange between marginal sea and open ocean have often been linked to upper-layer processes through vertical coupling (Cai et al, 2023;Hamilton et al, 2019;Quan et al, 2021; ∆OBP contains barotropic components associated with sea level differences in the upper layer and baroclinic components related to cross-strait density differences in the lower layer. Previous studies have confirmed that both the barotropic and baroclinic components of pressure contribute to the variability of the deep-layer LST (Cai et al, 2023;Song, 2006;Zhou et al, 2023;Zhu, Yao, et al, 2022).…”
Section: Telecommunications On the Oceanic Pathwaymentioning
confidence: 99%
“…Note that the amplitude of −∇•Q 1 P is comparable with, and even larger than, the canonical transfers in most areas. Recently, Quan et al [40] reported that the dominant energy source for the intraseasonal variability in the deep layer of the SCS was pressure work. The results from [40] and this study highlight that nonlocal eddy generation by pressure work is an important factor that should be considered when investigating eddy dynamics in the SCS.…”
Section: Wind Workmentioning
confidence: 99%
“…Recently, Quan et al [40] reported that the dominant energy source for the intraseasonal variability in the deep layer of the SCS was pressure work. The results from [40] and this study highlight that nonlocal eddy generation by pressure work is an important factor that should be considered when investigating eddy dynamics in the SCS. Different from other regions, the contributions of −∇•Q 1 P and canonical transfers are of opposite signs in the Kuroshio loop region, suggesting that pressure work acts to redistribute the mesoscale eddy energy generated by instabilities there.…”
Section: Wind Workmentioning
confidence: 99%
“…In the deep and middle layers, the exchanging currents are related to the density difference between the two basins (Qu et al., 2006; Y. T. Song, 2006), such as the numerical simulations (X. Wang et al., 2017; Zhao et al., 2014) showed that the intensified diapycnal mixing in the SCS basin induced the density gradient across the LS and maintained the deep intrusion. It is also noted that the variabilities of deep water exchange between marginal sea and open ocean have often been linked to the upper layer processes through vertical coupling (Hamilton et al., 2019; Quan et al., 2021; Tenreiro et al., 2018), such as the deep exchanging flow through the Yucatan Channel was well correlated with the variations in the upper Loop Current in the Gulf of Mexico (Bunge et al., 2002; Chang & Oey, 2011; Ezer et al., 2003).…”
Section: Introductionmentioning
confidence: 99%